Nemesia arenifera (Scrophulariaceae), a new species from the Sandveld, Northern Cape Province, South Africa, and the ectotypification of N. viscosa - Bester, Stoffel P.; Steyn, Hester M. (Phytotaxa, 2013)
Nemesia arenifera is described as a new species that has been overlooked since 1904. The name Nemesia viscosa was misapplied to specimens from the Namaqualand coast that was considered a coastal form of N. viscosa. Nemesia arenifera is a common and widespread plant on sandy soils in the coastal zone of Namaqualand, Northern Cape, while N. viscosa is only known from the original two gatherings made from one location in the Richtersveld, Northern Cape. The new species differs from N. viscosa and N. rupicola in habit, leaf and fruit shape, and by the orientation of the spur, which is similar to that of N. rupicola. A comparative table with diagnostic morphological features of N. arenifera, N. viscosa and N. rupicola is provided and a lectotype for N. viscosa is selected. Diagnostic characters of N. arenifera include the erect, sparsely branched habit, small yellow flowers, the orientation of the spur, and the densely viscid, glandular-pilose indumentum.